AGRITOURISM DEVELOPMENT: THE CASE OF SRI LANKA - MALKANTHI, PUSHPA (ASEAN Journal on Hospitality and Tourism, 2011)
The purpose of this research was to analyze the present status of agritourism development in Sri Lanka including issues and challenges of the sector. The study was based on a survey of agritourism operators in the country. Results revealed that only fifteen agritourism places are functioning currently with general services and facilities. Many destinations are operated by private companies and outside investors. Number of visitors and length of stay are at lower in many destinations. Further, there are several issues and challenges of the sector. Small size of the farm lands, lack of necessary skills, poor level of product development, poor publicity and promotion are important factors. While low numbers of visitors, environmental pollution, infrastructure development, are the common challenges for all the operators, monopoly of tour operators and political influence are the challenges for some operators including farmers those who conduct agritourism. Government intervention is essential to promote agritourism sector among the farming community of the country.